(3TQM CTcGd GdJCSjSs - (3ehSi Hf eMeO Hf eMehO GdQhej, UdGM GdOjf GdeYQha HbGVj RGOg ehSi LdHj , J fMh (B840 (3g` s; (3GdSeQbfOj , TeS GdOjf,J (B780 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb cd TF HbOQ hbOQ dg eG jdjb Hg s
(3BNQgG (B:s
(3ef KGfjI cJGH GdCUhd dEbdjOS hdjcf gPG BNQ GdcdGe s
(3GdfSNI HgG MhGTs
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs